Rethinking the Criminal Responsibility of Minors: A Comparative and Interdisciplinary Analysis - Ismanto; Suprapto; Nurunnisa (DIKTUM: Jurnal Syariah dan Hukum, 2026)
Background: The criminal responsibility of minors remains a pressing issue in contemporary legal studies because it lies at the intersection of justice, child protection, and societal security. Purpose: The aim of this paper is to critically analyze the legal and conceptual foundations of juvenile criminal responsibility, with particular attention to international human rights standards and comparative practices across jurisdictions. Methods: the study adopts a doctrinal and critical comparative approach, examining statutory frameworks, judicial interpretations, and scholarly debates while integrating insights from developmental psychology. Findings: The results reveal substantial inconsistencies in the age of criminal responsibility, limited compliance with the UN Convention on the Rights of the Child, and inadequate consideration of psychological maturity in determining culpability. Theoretical and Practical Implications: the study contributes to debates on the relationship between law, developmental science, and human rights in shaping juvenile justice frameworks. Practically, the findings underscore the need for policies that integrate restorative justice principles, prioritize rehabilitation over punitive measures, and harmonize domestic laws with international standards. Originality/Novelty: The originality of this research lies in its interdisciplinary critique that combines legal analysis, psychological insights, and human rights frameworks to propose an evidence-based recalibration of juvenile criminal responsibility .